Group portrait of Group #1 of the 1944 Mount Hermon Baptist Bible Conference - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing Group #1 of the Mount Hermon Baptist Bible Conference, held July 1944 at Mount Hermon, California.